Effects of Biology Learning Models on Metacognitive Skills of Senior High School Students - Ilham Majid; Roswita M Aboe; Anissa Novita Sari (Universitas Negeri Semarang, 2024)
The main problem in this study is that many students still rely on memorisation without understanding the concepts deeply, so their ability to plan, monitor and evaluate learning is less developed. In addition, conventional learning models that are often applied in schools tend to provide less opportunity for students to develop metacognitive skills optimally. Therefore, innovation is needed in learning models that can encourage students to think critically and reflect on their learning process. The purpose of this study was to determine the effect of STAD, guided inquiry, and combined STAD and guided inquiry learning models on the metacognitive skills of high school students in Ternate, Indonesia. The research used a quantitative method with a quasi-experimental nonequivalent control group design. The sample consisted of 92 active students in the even semester, selected through purposive sampling. In addition, metacognitive skills were measured using rubrics integrated with test questions. The results showed that the STAD learning model, guided inquiry and a combination of STAD and guided inquiry learning models can improve students' metacognitive skills with a value of Fhitung = 9.317. In addition, the use of STAD learning model, guided inquiry, and the combination of both models showed better metacognitive skills compared to the use of conventional methods. The conclusion of this research is that the learning model applied affects metacognition skills. The combination of STAD and guided inquiry learning models showed the highest achievement of metacognition skills compared to guided inquiry, STAD, and conventional learning models. However, the STAD and guided inquiry learning models showed the effect of metacognition scores that were not significantly different.